A FROM LITERATURE TO ANIMATION: DEFAMILIARIZATION TECHNIQUE IN TOM and JERRY - Yassir, Lazrak (MEDIOVA: Journal of Islamic Media Studies, 2023)
Defamiliarization is the artistic technique of making the audience perceive familiar objects in an unfamiliar way in order to enhance perception of the familiar. The term was first used in 1917 by Victor Shklovsky, one of the leading figures of the literary criticism movement known as Russian formalism. Victor Shklovsky’s Defamiliarization technique has been employed in various art forms, including animation, which primarily targets younger viewers. In this sense, William Hanna and Joseph Barbera’s creation Tom& Jerry is widely regarded as one of the greatest animated series of the 20th century. This iconic series is evidence of the popularity of animation and its ability to draw a large viewership for decades. With its innovative approach to visual storytelling, timeless humour, adorable characters, and -above all- its artistic use of defamiliarization technique, Tom & Jerry has left an indelible mark on the animation industry, entertaining viewers worldwide of all ages and soldifying its status as a true masterpiece. Based on the visual analysis method, this paper adapts Shklovsky’s technique of ‘defamiliarization’ from literature to animation, explaining its various aspects and considering its practical implications. The results obtained show that defamiliarization manifests itself multifariously in Tom & Jerry and that it can affect the perceptions of younger viewers who may misinterpret the defamiliarized visuals due to their cognitive immaturity.